2014
DOI: 10.1016/j.bpj.2013.11.1500
|View full text |Cite
|
Sign up to set email alerts
|

Structural Differences between the Closed and Open States of Channelrhodopsin-2 as Observed by Epr Spectroscopy

Abstract: untransfected cells retained high levels of this drug indicating that the MRP1 protein is functional. Using fluorescence recovery after photobleach (FRAP) we also demonstrated that the 2-color MRP1 is freely diffusible within the plasma membrane. 2-color MRP1 exhibited dynamic FRET changes in response to ATP and ATP þ substrate but not by substrate alone. FRET changes were quantified as an index of MRP1 conformational changes. These FRET changes correlate well with the available crystal structures which show c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…EPR spectroscopic measurements indicated that the dimers are tightly connected. 76,77 An oligomeric structure is not unusual for microbial rhodopsins, e.g. BR is organized as a trimer.…”
Section: General Structurementioning
confidence: 99%
See 1 more Smart Citation
“…EPR spectroscopic measurements indicated that the dimers are tightly connected. 76,77 An oligomeric structure is not unusual for microbial rhodopsins, e.g. BR is organized as a trimer.…”
Section: General Structurementioning
confidence: 99%
“…157 Furthermore, cryo-electron microscopic (cryo-EM) and electron paramagnetic resonance (EPR) spectroscopic measurements revealed movements of TM2, TM6 and TM7 during formation of the conducting state. 76,77,165 77,165 The MD simulation that led to the conclusions of the EHT-model was based on the C1C2 structure in which E3 forms a hydrogen bond to Asn258. 41 In contrast, the more recently released during the 15-anti cycle.…”
Section: Photocycle Modelsmentioning
confidence: 99%
“…Reprotonation of the RSB from the proton donor (D156) occurs simultaneously with channel closure during the decay of the conductive P 3 520 intermediate [7]. Electron paramagnetic resonance experiments on Cr ChR2 have shown that helices B and F move outwards upon formation of the conductive P 3 520 state [8]. Such helical movements persist even until the late desensitized P 4 480 state is formed [9].…”
Section: Introductionmentioning
confidence: 99%
“…Modern spin labeling applications also use orthogonal labeling schemes for proteins that contain functionally important cysteine side chains. 13,14 A summary of the rhodopsin studies is described below with discussions about the different directions of membrane protein EPR in the field. 8 and 9).…”
Section: Lydia N Caromentioning
confidence: 99%